Ecological and evolutionary response of Tethyan planktonic foraminifera to the middle Eocene climatic optimum (MECO) from the Alano section (NE Italy) - LUCIANI V; GIUSBERTI, LUCA; AGNINI, CLAUDIA; FORNACIARI, ELIANA; RIO, DOMENICO; SPOFFORTH DJA; PALIKE H. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
The enigmatic middle Eocene climatic optimum (MECO) is a transient (∼500 kyr) warming event that significantly interrupted at ∼40 Ma the long-term cooling through the middle and late Eocene, eventually resulting in establishment of permanent Antarctic ice-sheet. This event is still poorly known and data on the biotic response are so far scarce. Here we present a detailed planktonic foraminiferal analysis of the MECO interval from a marginal basin of the central-western Tethys (Alano section, northeastern Italy). The expanded and continuous Alano section provides an excellent record of this event and offers an appealing opportunity to better understand the role of climate upon calcareous plankton evolution. A sapropel-like interval, characterized by excursions in both the carbon and oxygen bulk-carbonate isotope records, represents the lithological expression of the post-MECO event in the study area and follows the δ18O negative shift, interpreted as representing the MECO warming. High-resolution quantitative analysis performed on both >38 μm and >63 μm fractions reveals pronounced and complex changes in planktonic foraminiferal assemblages indicating a strong environmental perturbation that parallels the variations of the stable isotope curves corresponding to the MECO and post-MECO intervals. These changes consist primarily in a marked increase in abundance of the relatively eutrophic subbotinids and of the small, low-oxygen tolerant Streptochilus, Chiloguembelina and Pseudohastigerina. At the same time, the arrival of the abundant opportunist eutrophic Jenkinsina and Pseudoglobigerinella bolivariana, typical species of very high-productivity areas, also occurs. The pronounced shift from oligotrophic to more eutrophic, opportunist, low-oxygen tolerant planktonic foraminiferal assemblages suggests increased nutrient input and surface ocean productivity in response to the environmental perturbation associated with the MECO. Particularly critical environmental conditions have been reached during the ...